Hybrid substations for low voltage distribution networks - Ganjavi, Amin (2019)
Voltage regulation has always been considered as the most important fundamental regulating functionalities in low voltage electrical power systems. The continuing trend toward heavier load and high penetration of distributed generation units in low voltage rural distribution feeders requires power electronic-based solution alternatives for voltage regulation purposes. The size of the power electronics is proportional to their power rating. The power rating of converters used for feeder voltage regulation is mainly based on substation voltage and feeder current which is influenced by load models. This thesis presents a powerful analysis based on probabilistic structure in order to find the required optimised power rating of the power electronics. This thesis also introduces a power electronic solution, known as a hybrid substation for voltage regulation purposes. The hybrid substation comprises fractionally rated power electronic four-leg voltage source converters with a conventional low frequency distribution transformer. An approach to minimise the compensated injection voltage of the hybrid substation using symmetrical components estimation has been presented. In this work, a comprehensive simulation study using MATLAB is carried out to analyse the optimum power rating of low voltage distribution power electronics based on statistics and probabilities. A simulation study using PLECS has been used to investigate the hybrid substation control performance. Furthermore, an experimental prototype has been built to validate the control algorithm.